2013
DOI: 10.1103/physrevc.88.034611
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of signatures of quasifission in reactions forming curium

Abstract: Background: Quasifission, a fission-like reaction outcome in which no compound nucleus forms, is an important competitor to fusion in reactions leading to superheavy elements. The precise mechanisms driving the competition between quasifission and fusion are not well understood. Purpose: To understand the influence reaction parameters have on quasifission probabilities, an investigation into the evolution of quasifission signatures as a function of entrance channel parameters is required. Methods: Using the Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 58 publications
(111 reference statements)
5
46
0
Order By: Relevance
“…Quasifission mass-angle distributions (MAD) first measured at GSI in the 1980s [2,5] showed that quasifission timescales could often be shorter than the rotation time of ∼10 −20 s. However, subsequently only a few measurements [6,7] were made until recent years, when an extensive series of experiments (using the Australian National University Heavy Ion Accelerator Facility and CUBE spectrometer) were carried out [3,[8][9][10][11][12][13][14][15][16]. The kinematic coincidence technique used in the measurements [2,3,17] provides direct information on the mass-ratio of the fragments at scission; thus, the data are represented in terms of mass ratio M R , rather than pre-or According to the characteristics of the MAD (minimum mass yield at symmetry, mass-angle correlation with peak yield at symmetry, and no significant mass-angle correlation), they are assigned as type MAD1, MAD2 and MAD3 respectively [3].…”
Section: Introductionmentioning
confidence: 99%
“…Quasifission mass-angle distributions (MAD) first measured at GSI in the 1980s [2,5] showed that quasifission timescales could often be shorter than the rotation time of ∼10 −20 s. However, subsequently only a few measurements [6,7] were made until recent years, when an extensive series of experiments (using the Australian National University Heavy Ion Accelerator Facility and CUBE spectrometer) were carried out [3,[8][9][10][11][12][13][14][15][16]. The kinematic coincidence technique used in the measurements [2,3,17] provides direct information on the mass-ratio of the fragments at scission; thus, the data are represented in terms of mass ratio M R , rather than pre-or According to the characteristics of the MAD (minimum mass yield at symmetry, mass-angle correlation with peak yield at symmetry, and no significant mass-angle correlation), they are assigned as type MAD1, MAD2 and MAD3 respectively [3].…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed beams ranging from (f-j) Mass ratios for each studied reaction, compared with a single (red) or, where applicable, a dual (blue) Gaussian fit, as described in Ref. [18]. For all results in this figure, only one energy for each reaction is shown for brevity; similar results were obtained for other excitation energies.…”
Section: Methodsmentioning
confidence: 68%
“…A summary of the reactions chosen and any relevant reaction parameters is provided in Table I of Ref. [18].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations